Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s00464-019-06907-7
|View full text |Cite|
|
Sign up to set email alerts
|

Update of Guidelines for laparoscopic treatment of ventral and incisional abdominal wall hernias (International Endohernia Society (IEHS))—Part A

Abstract: In 2014, the International Endohernia Society (IEHS) published the first international "Guidelines for laparoscopic treatment of ventral and incisional abdominal wall hernias." Guidelines reflect the currently best available evidence in diagnostics and therapy and give recommendations to help surgeons to standardize their techniques and to improve their results. However, science is a dynamic field which is continuously developing. Therefore, guidelines require regular updates to keep pace with the evolving lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(214 citation statements)
references
References 2 publications
(2 reference statements)
10
180
0
24
Order By: Relevance
“…Finally, the extent of separation must exceed the defect by at least 5 cm. In our study, the association between the mesh area and defect size area was according to the guidelines for the prevention of a recurrence, which was far more than 16:1 [23,24].…”
Section: Discussionmentioning
confidence: 76%
“…Finally, the extent of separation must exceed the defect by at least 5 cm. In our study, the association between the mesh area and defect size area was according to the guidelines for the prevention of a recurrence, which was far more than 16:1 [23,24].…”
Section: Discussionmentioning
confidence: 76%
“…The International Endohernia Society guidelines concluded that TAPP had longer operative times and longer hospital stays than TEP, but they noted that TEP has more intraoperative and postoperative complications. These guidelines also found both TAPP and TEP to be an acceptable treatment option for inguinal hernia repair .…”
Section: Evidence In the Literaturementioning
confidence: 98%
“…The most important argument for this recommendation is the increasing complexity of abdominal wall surgery due to new techniques, more difficult cases, a recognized tailored approach and an increasing public awareness which demands nothing short of optimal treatment results [1]. The rising complexity of abdominal wall surgery has led to the international hernia societies publishing several guidelines [2][3][4][5][6][7][8][9][10][11][12][13][14]. However, more work is required to define in the scientific literature the growing evolution and complex nature of contemporaneous abdominal wall surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines to date take into account developments in abdominal wall surgery and issue evidence-based recommendations for the best possible contemporary practices in abdominal wall surgery [2][3][4][5][6][7][8][9][10][11][12][13][14]. The scope of these guidelines clearly provides information as to how complex abdominal wall surgery has now become and consideration of the myriad of technical details in abdominal wall surgery will inevitably help contribute to the preferred good outcomes [2][3][4][5][6][7][8][9][10][11][12][13][14]. Notwithstanding a clinician's relative experience with the use of a tailored approach for hernia repair, mastery of a single surgical technique is now recognized as possibly insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation